Digital Marketing “Optimization” Business Training for Disdagin Bandung - Endang AF; Iwan Rijayana; Dani Hamdani; M. Benny Chaniago (BULLET : Jurnal Multidisiplin Ilmu, 2022)
− MSME (Micro, Small and Medium Enterprises) is a type of business that is in great demand by the people of Indonesia. The ease of adopting innovation in business and especially in technology is one of the main advantages of MSMEs. The development of MSMEs in Indonesia is experiencing good growth every year. However, since March 2020, a virus whose presence has disrupted the existing order, especially in terms of the economy, is the corona virus. In Indonesia itself, especially in West Java, the Large-Scale Social Restrictions (PSBB) policy was implemented to suppress the spread of this virus, which resulted in the economy of West Java, one of which was slumped by experiencing a contraction of minus 5.90. This condition forces MSMEs who are members of the Department of Trade and Industry (DISDAGIN) of Bandung City. Around 6000 MSME products assisted by DISDAGIN Bandung City to digitize in order to maintain their business through optimization of marketing content, the use of SEO, SEM, advertising and optimization of customer needs which will be implemented in their business, so that it is expected to boost product marketing to a greater reach. This research method includes 6 stages which result in practical training accompanied by lecturers and students of Information Systems Study Program of Widyatama University.